Założenia organizacyjne żłobków dziennych w okresie międzywojennym według wytycznych Polskiego Komitetu Opieki nad Dzieckiem - Wróblewska, Urszula (Biuletyn Historii Wychowania, 2023)
The aim of this article is to present the main organizational assumptions of nurseries, which were just organized in the Interwar period and were to represent the first level of social care and educational work for mothers and children. The proposed issue is of contributory nature and is the first attempt to discuss the activities and operations of nurseries in the Interwar period, when their utility and significance were discussed. It is a description of the origins of the facility, which in the post-war period was a common element of childcare. As a result of the developing industry and the growing demand for workers, young mothers also took up paid jobs in order to improve their material status. Therefore, nurseries located near factories did not actually mushroom and the time of development of this institution was arrested in the post-war period.